A brief analysis method in plant landscape design of motorway. Issue 1 (March 2021) - Que, Yi; Tang, Haiyan; Zhang, Zhiwei; Zhao, Hengyi
Abstract: Plant landscape design is one of the main contents of highway design. This paper sums up the principles and methods for plant landscape design based on the compositions of expressway landscape, and discusses in detail the point of plant landscape design for the green belt on both sides of the expressway, the central separation belt and the subsidiary green area.